The STRATEGI PROMOSI FESTIVAL LAMPION SEBAGAI IKON BUDAYA DI KOTA PALEMBANG - Ismi Maharani; Agus Srimudin; Adli (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2025)
Tourism is one of the efforts of regional revenue in exploring sources of local original income (PAD) so that income from the tourism sector gets many visits from within the country and abroad or abroad. The Palembang city government needs to make all events, but tourist destinations are almost in all regions, that is the need for a promotional strategy carried out by the Palembang City Tourism Office. This study aims to find out how the strategy of promoting the lantern festival as a cultural icon in the city of Palembang. This research uses a descriptive qualitative approach, This research uses data collection methods in the form of in-depth interviews, direct observations, and documentation studies. The data analysis techniques used in this study are data reduction, data presentation and Conclusion Drawing and Verification. The results of the study show that the Lantern Festival promotion strategy in Palembang City is designed to strengthen its position as a cultural icon that attracts local, national, and international tourists. The approach used includes a promotional mix such as advertising, public relations, personal selling, and direct marketing. The use of social media is one of the important elements to reach the younger generation who are exposed to global culture.